The Analyze Of Health Service Utilization With The Compliance Of Paying Premium On The Independent Bpjs Participants Who Seek Treatment In Unit In Dr Iskak Tulungagung Hospital - Bagus Puspita Aji; Sandu Siyoto; Aprin Rusmawati (Universitas STRADA Indonesia, 2020)
Many people take advantage of the BPJS program me as an alternative to the issue of health care expenses using the cost insurance system so light. The problem is because of the patients who experienced delay paying premium / dues BPJS every month so that can not take advantage of health services. The purpose of this research is to know the relationship of health service utilization with the compliance of paying premium on the independent BPJS participants who seek treatment in Unit In Dr Iskak Tulungagung Hospital. The design of this study was observational with cross sectional approach. The population in this study were all patients of independent BPJS who treated in Unit In Dr. Iskak Tulungagung Hospital on average monthly number of 2500 patients. The sample is part of the population that is 80 respondents with accidental sampling technique. The data that have been collected is processed by chi square statistic test with significance α = 0,05. The results showed that from 80 respondents, most of respondents use BPJS service, that is 49 respondents (61,2%) and most of respondent pay BPJS premium regularly, that is 48 respondent (60,0%). The result of chi square test analysis obtained p-value = 0,005 (<0,05) which means reject H0 and accept H1 so that there is relation of health service utilization with compliance pay premium to participant of BPJS independent in Unit In Dr Iskak Tulungagung. Utilization of health services BPJS maximally will provide optimal health benefits that will make respondents realize the importance of paying premiums regularly in order to take advantage of health services.